Magnetic properties, magnetic transition and large magneto-caloric effect in the Ho0.2Er0.2Tm0.2Ni0.2Cu0.2 amorphous ribbon. (1st April 2022) - Yao, Kai; Xu, Yan
Abstract: The magneto-caloric (MC) effect in rare earths ( RE ) based magnetic materials have been extensively investigated in recent years not only due to the potential applications in the field of cryogenic magnetic refrigeration (MR) technology but also for better understanding the magnetic properties and magnetic transition of these materials. In this work, we reported a systematical investigation of the cryogenic magnetic and MC properties in the RE -based equi-atomic Ho0.2 Er0.2 Tm0.2 Ni0.2 Cu0.2 amorphous ribbon. The Ho0.2 Er0.2 Tm0.2 Ni0.2 Cu0.2 amorphous ribbon reveals a second order magnetic transition (SOMT) at ∼11.5 K from paramagnetic to ferromagnetic states. Large reversible MC effect and promising MC performances were found in the Ho0.2 Er0.2 Tm0.2 Ni0.2 Cu0.2 amorphous ribbon, and the MC parameters of the maximum isothermal magnetic entropy changes (-Δ S M max ) as well as the refrigerant capacity/relative cooling power ( RC/RCP ) under the magnetic field change of 0–50 kOe are evaluated to be 15.44 J/kgK and 317.4/397.2 J/kg, respectively. Highlights: The Ho0.2 Er0.2 Tm0.2 Ni0.2 Cu0.2 amorphous ribbon was fabricated. The magnetic properties in Ho0.2 Er0.2 Tm0.2 Ni0.2 Cu0.2 were studied. Large magneto-caloric effect in Ho0.2 Er0.2 Tm0.2 Ni0.2 Cu0.2 was observed.